Two-Dimensional Analysis of Lower Extremities to Predict Best Initial Condition on Marching Movement - Faisal Afif, Daffa; Made Ayu Sinta Dewi, Ni; Irham Naufran, Denis; Paskalis, Felix; Ferryanto, Ferryanto (Mesin, 2023)
Himpunan Mahasiswa Mesin ITB has a specific type of marching that follows a march song’s rhythm called “derap”. In practice, derap was a hard move to maintain and unify in a group. This difficulty was observed by noting the differences that occur between the subjects' initial and middle march motion conditions. The most noticeable difference was the height of the group. This study intends to observe and find how the differences vary in this motion. The differences that occur corresponded to the relative knee and ankle angle. This study utilized five active markers to reconstruct the lower extremities' activity during motion, one action camera at 60 fps, and a workstation. This study was also constrained by using three cycles of march song at 115 bpm. Direct Linear Transformation was used to obtain the intrinsic factor of the camera to reconstruct the motion. Evaluating the angular kinematic parameters of relative knee and ankle angle, the authors found the relative knee angle has increased from 110° to around 130°, which happened at the second song cycle and kept stable at the rest of the song. This result brought the conclusion that more extended derap motion would tend to a steady condition of relative knee angle and suggested that the subject should begin with 130° of relative knee angle to give less effort on marching.